Red cell alloimmunization in multitransfused chronic renal patients on haemodialysis in a tertiary care centre of Jammu region - Sawhney, Vijay; Dutt, Neeti; Sharma, Sushil; Khajuria, Kajal (International Journal of Advances in Medicine, 2018)
Background: There is a high incidence of alloimunization in many patients with diseases that require repetitive blood transfusions. One such group is chronic renal failure patients as majority of them have severe anemia due to deficiency of erythropoietin. As many such patients are unable to afford erythropoietin, they are treated with blood transfusions. This study was thus undertaken to study alloimunization in such patients at our center. Methods: A total of 96 patients found eligible were enrolled in this cross-sectional study that was carried out from June 2016 to august 2016. After detailed history, antibody screening was done by using Immucor Panoscreen three vial set and if screening came out to be positive antibody identification was then done by using Immucor Panocell-10. Results: 96 patients including 76 male and 20 female patients recieved a total of 912 transfusions. Alloantibodies were detected in a total of 12 patients (12.5%). Of these 12 patients 8 patients had a single antibody whereas 4 patients developed two antibodies. The antibodies developed at a rate of 1.8% per transfusion (16/912). On alloantibody type identification, the most common type found was anti E (4/16) followed by both anti D and anti C in 3 patients each. Conclusions: Alloimmunization to minor erythrocyte antigens occurs in many patients of chronic renal failure. This results in frequent pre-and post-transfusion complications. Inclusion of antibody screening test in routine pretransfusion testing protocol for the patients who are at higher risk of alloimmunization and require long-term transfusion dependence is desirable.